2008
DOI: 10.1103/physrevd.77.043510
|View full text |Cite
|
Sign up to set email alerts
|

Leptogenesis with many neutrinos

Abstract: We consider leptogenesis in scenarios with many neutrino singlets. We find that the lower bound for the reheating temperature can be significantly relaxed with respect to the hierarchical three neutrino case. We further argue that the upper bound for the neutrino mass scale from leptogenesis gets significantly lifted in these scenarios. As a specific realization, we then discuss an extra-dimensional model, where the large number of neutrinos is provided by Kaluza-Klein excitations. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In contrast, the contribution of many singlets in weak washout can enhance the final baryon asymmetry, allowing thermal leptogenesis at T reheat that is a factor ∼30 lower than in the case of three singlet neutrinos [175]. In the case where leptogenesis is unflavoured, extra singlets weaken the upper bound on | | from 3M 1 [175,176]. 4.…”
Section: Cp Violation In N 1 Decaysmentioning
confidence: 82%
“…In contrast, the contribution of many singlets in weak washout can enhance the final baryon asymmetry, allowing thermal leptogenesis at T reheat that is a factor ∼30 lower than in the case of three singlet neutrinos [175]. In the case where leptogenesis is unflavoured, extra singlets weaken the upper bound on | | from 3M 1 [175,176]. 4.…”
Section: Cp Violation In N 1 Decaysmentioning
confidence: 82%
“…An upper limit on the KK masses M n (H i ) is set by the graviton bound [32,33], i.e. by the requirement that late decays should not spoil the production of light elements during Big Bang nucleosynthesis (BBN) at T BBN ∼ 0.3 MeV.…”
Section: Bounds On Yukawa Couplingsmentioning
confidence: 99%
“…Let us also mention that meanwhile the many neutrino scenario has been analyzed in some detail. It has been found that many neutrinos somewhat relax the tension between leptogenesis and supersymmetry [112,113]. Furthermore, the presence of many neutrinos and their Yukawa couplings have important consequences for supersymmetric lepton flavor violation [113].…”
Section: How Good Are the Mini-landscape Models?mentioning
confidence: 99%